The impact of cryopreservation on the morphology of spermatozoa in men with oligoasthenoteratozoospermia - Yurchuk, Taisiia; Petrushko, Maryna; Gapon, Anna; Piniaiev, Volodymyr; Kuleshova, Lilia (Cryobiology, 2021)
The cryopreservation of ejaculate can reduce the viability, motility, and morphological characteristics of the spermatozoa of infertile men. Oligoasthenoteratozoospermia (OAT) is the most common cause of male subfertility. The aim of this study was to evaluate the morphological characteristics and viability of progressive motile sperm fraction before and after cryopreservation, and to determine whether cryopreservation of progressive motile sperm fraction is effective in eliminating morphologically abnormal sperm in men with OAT. An increased proportion of spermatozoa with normal morphology in fresh progressive motile sperm fraction compared with fresh ejaculate has been observed. After cryopreservation, the motility was 65.5 ± 8.8%; the proportion of spermatozoa with normal morphology increased non-significantly compared with freshly prepared motile sperm fraction (35.6 ± 5.5%). Concurrently, the proportion of cryopreserved spermatozoa with head defects increased significantly by 1.7 times (to 38.4 ± 4.7%) and the proportion of almost all morphologically abnormal sperm cells, particularly spermatozoa with multiple abnormalities, was reduced significantly. These data appear to be a novel finding in the context of patients with OAT. Using such spermatozoa for in vitro fertilization leads to a significant decrease in both a number of embryos at the cleavage stage and the blastocysts formation rate. High-magnification sperm morphology examination and selection, IMSI, post-cryopreservation significantly increased the likelihood of successful oocyte fertilization and subsequent embryo development.
Keywords: Oligoasthenoteratozoospermia; Assisted reproduction; Spermatozoa morphology; Cryopreservation; Semen analysis